Investigating a Secondary EFL Teacher’s Practices of Using Translanguaging in Teaching Speaking: A Descriptive Case Study - Khoerunnisa, Fyna Farhan; Yanto, Elih Sutisna; Saefullah, Hilmansyah (Journal of Educational Sciences, 2024)
English is now increasingly used by non-native speakers and translanguaging can be used by all teachers to ensure that students understand the subject matter throughout the teaching speaking process. This study aims to examine the teacher's practices and intentions regarding the use of translanguaging in teaching speaking and to examine how EFL students respond to translanguaging practices in EFL speaking classroom. This is a descriptive case study focusing on an EFL teacher and five EFL students in a vacational high school setting. Data collection methods include observation and semi-structured interviews using thematic data analysis. The results show translanguaging practice occurred in speaking classroom, which served several purposes including to encourage student's active participation, reinforce learning, provide specific areas of improvement, and provide model repetition. The students responded positively to the use of translanguaging, finding it facilitates a quick understanding, makes less fluent in English and helpful in understanding the lessons in speaking classroom. They emphasised the benefits of translanguaging and preferred to use it because it can be an effective strategy to address the challenges of learning speaking. The study concludes that allowing students to use their native language when speaking classroom can improve comprehension.